The 4th Industrial Revolution Effects on Industrial Production of South Africa - Sikhakhane, Felihle; David, Oladipo Olalekan; Wyk, Abigail Stiglingh-Van (International Journal of Economics and Financial Issues, 2023)
This study examines how critical South Africa’s response to the fourth industrial revolution industrial production. In a developing continent like Africa technological advancements have been rather slow, and adapting to those technological changes has been challenging. Since the age of artificial intelligence entered the economic market and there is an increased demand to implement more Artificial intelligence in production. This study looks at how can more fourth industrial production be employed without having an impact on markets like employment, and whether is it a given possibility with the low levels of energy generation, ICT investment, industrial production performance, ICT development, and human capital development. The endogenous growth framework frameworks evaluate the statistical significance elements of economic growth, such as investments in human capital, knowledge, and innovation. The Cobb-Douglas production functions framework shows the technological connection between two or more inputs and how much output they may produce. These results show the correlation between non-stationary time sequences over the long term and for a given time period. The six variables and total industrial production in the study revealed positive correlations between growth and human capital investments and causation. This means that growth benefits are to some degree being directed toward the improvement of the skill sector and financing. This indicates that the industrial sector supported the labour market.